The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1136/bmj.k5317
|View full text |Cite|
|
Sign up to set email alerts
|

The timing is right to end snakebite deaths in South Asia

Abstract: Regional collaboration is crucial to end preventable deaths and disability from snakebites in South Asia, say Ravikar Ralph and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 53 publications
1
65
0
1
Order By: Relevance
“…To meet the requirement of antivenoms, snake antivenom sera are presently also imported from India. However, studies have shown that Indian antivenoms provide partial neutralization, particularly for N. naja venom [ 14 , 15 , 16 ]. Although, N. naja and N. oxiana are also prevalent in India, but the venom composition is known to vary within the same species, due to change in geographical and ecological factors [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…To meet the requirement of antivenoms, snake antivenom sera are presently also imported from India. However, studies have shown that Indian antivenoms provide partial neutralization, particularly for N. naja venom [ 14 , 15 , 16 ]. Although, N. naja and N. oxiana are also prevalent in India, but the venom composition is known to vary within the same species, due to change in geographical and ecological factors [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cerastes gasparetti (7) Boiga sp. (4) Cerastes vipera (1) Boiga trigonata (4) Daboia russelii (985) Chrysopelea ornata (1) Daboia siamensis (383) Chrysopelea pelias (1) Echis carinatus (229) Coelognathus helena (5) Echis coloratus (5) Coelognathus radiatus (4) Hydrophis cyanocinctus (2) Cylindrophis maculatus (1) Hydrophis platurus (2) Cylindrophis ruffus (NR) Naja spp.…”
Section: Africamentioning
confidence: 99%
“…(4) Cerastes vipera (1) Boiga trigonata (4) Daboia russelii (985) Chrysopelea ornata (1) Daboia siamensis (383) Chrysopelea pelias (1) Echis carinatus (229) Coelognathus helena (5) Echis coloratus (5) Coelognathus radiatus (4) Hydrophis cyanocinctus (2) Cylindrophis maculatus (1) Hydrophis platurus (2) Cylindrophis ruffus (NR) Naja spp. (8) Lycodon striatus (15) Naja sumatrana (1) Malpolon moilensis (4) Ovophis monticola (1) « non-venomous snakes » (53) Rhabdophis subminiatus (5) Oligodon arnensis (7) Trimeresurus albolabris (344) Oligodon cyclurus (NR) Trimeresurus gramineus (20) Oligodon spp (7) Trimeresurus kanburiensis (1) Oligodon taeniatus (NR) Trimeresurus macrops (23) Oligodon taeniolatus (2) Trimeresurus malabaricus (26) Pareas carinatus (NR) Trimeresurus purpureomaculatus (3) Psammodynastes pulverulentus (2) Trimeresurus spp. (36) Ptyas mucosa (13) Trimeresurus trigonocephalus (19) Ptyas spp.…”
Section: Africamentioning
confidence: 99%
See 1 more Smart Citation
“…O soro liofilizado não necessita de cadeia de frio. Na Índia, são disponibilizadas as duas apresentações de antiveneno, sendo que a liofilizada permite que o tratamento seja realizado nas zonas mais distantes do país, onde não há cadeia de frio 32 . O retardo no tratamento soroterápico pode aumentar os riscos de complicações, particularmente de insuficiência renal aguda, agravando o quadro clínico e piorando seu prognóstico, podendo evoluir com sequelas e a óbito 27 .…”
Section: Descrição Do Casounclassified